First report of the genus Longipalpus Montrouzier, 1861 (Coleoptera: Cerambycidae: Cerambycinae) from India with the description of a new species - Hiremath, S. R. (Zootaxa, 2020)
Longipalpus palodensis sp. nov. (Cerambycidae: Cerambycinae: Obriini) is described and illustrated from India. Life history information is also provided. This is the first report of the genus from India.